Development of the tectonic structure of the Cuu Long basin in Cenozoic - Viet, Le Trieu; Chinh, Vu Van; Thang, Tran Van; Tung, Van Duc; Ha, Le Thanh; Huong, Nguyen Thi Thanh; Linh, Phan Doan; Nam, Dao Hai; Quynh, Bui Van (Vietnam Journal of Earth Sciences, 2012)
Based on published documents, data of wells and also activity fault systems related with Cuulong basin, the authors drew up three following sketched maps: the sketched map of total tectonic subsidence of Cuu Long basin; of Neotectonic structure and sketched map of allocation of Tertiary sediment in Cuu Long basin. On these sketched maps one can see the development of the tectonic structure of basin, that has close relation with the active fault systems and state regional geodynamics. The process of formation and development of structure may be divided into three stages: first stage from Middle Eocene to Late Oligocene, second stage from Early Miocene to Late Miocene and third stage from Pliocene to Holocene. The first stage was divided into 2 phases of stretching and at the end of each phase corresponding the phase of compression. In the early stretching phase the sub-basins are formatted, and in the late one these sub-basins are linked into large united lake in center of basin. In each phases of compression there are anticlinal structures are formatted. In second stage the basin developed with thermal subsidence and enlarged to westward. Miocene structrural plane tenderly covered on the former plane. In the latest stage (Pliocene - Quaternary) the development of the basin is the largest in comparison to previous stages. And after some times of impaction by raising and lowering of sea level it is stabilizing under sea level from Holocene epoch to present.